Aspartic Proteases and Major Cell Wall Components in Candida albicans Trigger the Release of Neutrophil Extracellular Traps - Zawrotniak, Marcin; Bochenska, Oliwia; Karkowska-Kuleta, Justyna; Seweryn-Ozog, Karolina; Aoki, Wataru; Ueda, Mitsuyoshi; Kozik, Andrzej; Rapala-Kozik, Maria (Frontiers in Cellular and Infection Microbiology, 2017)
Neutrophils use different mechanisms to cope with pathogens that invade the host organism. The most intriguing of these responses is a release of neutrophil extracellular traps (NETs) composed of decondensed chromatin and granular proteins with antimicrobial activity. An important potential target of NETs is Candida albicans – an opportunistic fungal pathogen that employs morphological and phenotype switches and biofilm formation during contact with neutrophils, accompanied by changes in epitope exposition that mask the pathogen from host recognition. These processes differ depending on infection conditions and are thus influenced by the surrounding environment. In the current study, we compared the NET release by neutrophils upon contact with purified main candidal cell surface components. We show here for the first time that in addition to the main cell wall-building polysaccharides (mannans and β-glucans), secreted aspartic proteases (Saps) trigger NETs with variable intensities. The most efficient NET-releasing response is with Sap4 and Sap6, which are known to be secreted by fungal hyphae. This involves mixed, ROS-dependent and ROS-independent signaling pathways, mainly through interactions with the CD11b receptor. In comparison, upon contact with the cell wall-bound Sap9 and Sap10, neutrophils responded via a ROS-dependent mechanism using CD16 and CD18 receptors for protease recognition. In addition to the Saps tested, the actuation of selected mediating kinases (Src, Syk, PI3K and ERK) was also investigated. β-Glucans were found to trigger a ROS-dependent process of NET production with engagement of Dectin-1 as well as CD11b and CD18 receptors. Mannans were recognized by TLRs, CD14 and Dectin-1 receptors and triggered NET release mainly via a ROS-independent pathway. Our results strongly suggest that neutrophils activate NET production in response to different candidal components that are presented locally at low concentrations at the initial stages of infection. However, NET release seemed to be blocked by increasing numbers of fungal cells.